2022
DOI: 10.1371/journal.pgph.0001333
|View full text |Cite
|
Sign up to set email alerts
|

Resource availability and barriers to delivering quality care for newborns in hospitals in the southern region of Malawi: A multisite observational study

Abstract: Facility-based births have increased in low and middle-income countries, but babies still die due to poor care. Improving care leads to better newborn outcomes. However, data are lacking on how well facilities are prepared to support. We assessed the availability of human and material resources and barriers to delivering quality care for newborns and barriers to delivering quality care for newborns. We adapted the WHO Service Availability and Readiness Assessment tool to evaluate the resources for delivery and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Scarcity of resources and a lack of trained staff are among the contributory factors for these deaths. 26 - 28 Our study also revealed that survival rates decline more rapidly in Pakistan than in India. These findings in Pakistan can be attributed to issues of healthcare access and quality, as well as a lack of a national policy on neonatal health.…”
Section: Discussionsupporting
confidence: 54%
“…Scarcity of resources and a lack of trained staff are among the contributory factors for these deaths. 26 - 28 Our study also revealed that survival rates decline more rapidly in Pakistan than in India. These findings in Pakistan can be attributed to issues of healthcare access and quality, as well as a lack of a national policy on neonatal health.…”
Section: Discussionsupporting
confidence: 54%
“…The results demonstrated that the development of the ward led to signi cant improvement over the study period in neonatal mortality, aligning with increased resources, including space, assigned neonatal sta ng with dedicated training and mentorship, and appropriately available equipment, medications and supplies. This is critical, as several studies in similar contexts within sub-Saharan Africa have shown that neonatal care provision in rural resource-limited settings remains a challenge [2,5,24,27,33]. This study suggests, however, that with similar inputs and improvements as in Neno, comparable improvements in neonatal survival are possible [35][36][37].…”
Section: Discussionmentioning
confidence: 83%
“…[27][28][29][30] Limited resources and infrastructure pose significant challenges in delivering optimal care to neonates. [31][32][33][34] The shortage of skilled healthcare professionals further exacerbates this issue, as it hampers the ability to provide timely interventions and specialized treatments. [35][36][37] Furthermore, contextualizing these factors within the Ghanaian healthcare system sheds light on additional gaps in research and theories concerning neonatal care.…”
Section: Standards Of Care In Neonatal Care Systemsmentioning
confidence: 99%